Хірургічне лікування гіперпаратиреозу - Завгородній, С. М.; Вільховой, С. О.; Поляков, М. М.; Гайдаржі, Є. І. (Clinical Endocrinology and Endocrine Surgery, 2009)
In the article the results of surgical treatment of 81 patients with a hyperparathyroidism from which 32 patients with a primary hyperparathyroidism, 36 — with a secondary and 13 — with a tertiary hyperparathyroidism are given. In all patients after operations normalization of laboratory indicators and regression or full absence of clinical sings of disease have been shown.